1995
DOI: 10.1111/j.1365-2605.1995.tb00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Myoid cell proliferation in rat seminiferous tubules after ischaemic testicular atrophy induced by epinephrine. Morphometric and immunohistochemical (bromo‐deoxyuridine and PCNA) studies*

Abstract: The proliferation of peritubular myoid cells in the testes of rats treated for 1-11 weeks with intra-scrotal injections of epinephrine was investigated using immunohistochemistry and quantitative histology. The percentage of peritubular cells that were immunopositive for proliferating cell nuclear antigen (PCNA) or that were labelled with 5'-bromodeoxyuridine (BrdU) in the S-phase of the cell cycle, were calculated in control and treated rats after 1,3,5,8 and 11 weeks of treatment. In addition, the change in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
3
9
1
Order By: Relevance
“…The increase in fibronectin immunostaining detected at the end of experiment in the present study may be related to the synthesis of type I collagen, which is abundant in the tubular lamina propria (Hadley & Dym, 1987). This collagen production, together with the increased formation of laminin and fibronectin, would be involved in enlargement of the tunica propria and fibrosis reported previously in epinephrine-treated rat testes at advanced stages of the experiment (Santamaria et al, 1995). .…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The increase in fibronectin immunostaining detected at the end of experiment in the present study may be related to the synthesis of type I collagen, which is abundant in the tubular lamina propria (Hadley & Dym, 1987). This collagen production, together with the increased formation of laminin and fibronectin, would be involved in enlargement of the tunica propria and fibrosis reported previously in epinephrine-treated rat testes at advanced stages of the experiment (Santamaria et al, 1995). .…”
Section: Discussionsupporting
confidence: 74%
“…The cooperation between Sertoli cells and peritubular myoid cells in the synthesis of extracellular matrix components of the tubular lamina propria, including glycosaminoglycans, collagen and laminin, is well known (Raychoudhury et al, 1992(Raychoudhury et al, , 1993a. A previous study of epinephrine-treated rat testes, using BrdU labelling, showed that the proliferation rate of peritubular myoid cells increase4during the first 8 weeks of treatment and decreased thereafter (Santamaria et al, 1995). Perhaps peritubular cell proliferation inhibits other functions of these cells, including their cooperation with Sertoli cells, which would temporarily decrease laminin synthesis; this would then return to normal values when proliferation ceased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the human adult testis, PCNA-staining are consistently detected in spermatogonia and early spermatocytes but hardly detected in the interstitial cells (Hall et al, 1990). However, PCNA can be also used as a marker for proliferation of testicular interstitial cells (Santamaria et al, 1995;Tauber et al, 1995;Schlatt et al, 1999;Murray et al, 2000). In the present study, it was found that not only germ cells but also other testicular cells during 70-90 days of gestation had been detected by a positive PCNA monoclonal antibody reaction.…”
Section: Discussionsupporting
confidence: 51%
“…We chose three 5‐m sections (25 random fields per section) and calculated following histomorphometric variables using the Cell D Olympus image analysis software: (i) the volume density of seminiferous tubules (VD ST ), as the seminiferous tubule surface/reference area (142,049.28 m 2 ) ratio; (ii) the testicular interstitium volume density (VD TI ), as the ratio of interstitium surface/reference area (142,049.28 m 2 ) ratio; (iii) the total volume of seminiferous tubule per testis ( V ST ) multiplying VD ST V T ; and (iv) the length of seminiferous tubule per volume unit ( L v ) using the established formula: L v = VD ST / R 2 (Santamaría, Martín, Codesal, & Paniagua, ). In addition, for the total length of seminiferous tubules ( L ST ), we assumed that all tubules form a single cylinder with a length L , a radius R (MTD/2) and a volume V ST .…”
Section: Methodsmentioning
confidence: 99%